ARABIC LINGUISTIC IN TRANSOXIANA (XI-XIII CENTURIES) - Kasimova Sarvinoz Sayfullaevna (International Journal of Innovative Technologies in Social Science, 2019)
The study was aimed to determine the research work which were done about Arabic linguistics in XI-XIII century in Transoxiana, especially, shows that lexicography of Arabic language, lexicology, theoretical basis of its grammar have been investigated.